FIRST STEPS FOR MODERNIZATION OF WATER FARMING IN THE REPUBLIC: ACHIEVEMENTS AND CHALLENGES (Euro-Asia Conferences, 2021)
The article analyzes the implementation of reforms in the watermanagement system in Uzbekistan during the years of independence,special attention to the rational and economical use of water resourcesin the irrigation system, the gradual improvement of modernization inthe industry. In this regard, during this period, a number of decisions,laws were developed and implemented in order to develop the systemand legally guarantee it.